Research Progress on Nutritional Characteristics, Taste Quality Improvement and Functional Evaluation of Germinated Brown Rice - REN Chuanying, HONG Bin, ZHANG Shan, YUAN Di, FENG Junran, SHAN Shan, ZHANG Jingyi, GUAN Lijun, LI Bo, HUANG Wengong, LU Shuwen (Shipin Kexue)
Germinated brown rice (GBR) is a whole grain containing the intact bran and embryo, concentrating most nutrients and functional active compounds. However, the dense fiber structure of the bran hinders the rate and capacity of water absorption and starch gelatinization during cooking. Therefore, compared with white rice, GBR has poorer cooking and eating quality, and they cannot be cooked at the same time. For this reason, GBR is not widely accepted by consumers. This article reviews the physiological metabolic reactions of GBR and the changes in nutritional components, bioactive substances, and taste quality during germination. It also summarizes and analyzes the current status of research on stress enrichment of γ-aminobutyric acid (GABA) and functional characteristics of GBR. During germination, enzymes promote the enrichment of various bioactive substances, especially GABA, a characteristic component. The enrichment of GABA can be promoted by various stress conditions with changing Ca2+, H+ or substrate levels. Some pretreatment techniques are available to further improve the taste quality of GBR. GABA works synergistically with other nutrients and active ingredients to endow GBR with a series of biological functions such as anti-hyperlipidemia, anti-hyperglycemia, heart protection, sleep improvement, anti-inflammatory and antioxidant effects.